Nerwiakowłókniakowatość typu 1 - choroba wymagająca wielodyscyplinarnej opieki specjalistycznej - Ziółkowska, Adriana; Glińska, Katarzyna; Szymańska, Sylwia; Jóźwiak, Sergiusz (Pediatria Polska - Polish Journal of Paediatrics, 2017)
Neurofibromatosis type 1 (NF1) is a relatively frequent genetic disorder inherited in an autosomal dominant fashion and the most common phakomatosis. The disease can affect many organs and systems, mainly the skin, bones and nervous system, but manifestations are extremely variable, even within a family. Patients have an increased risk of benign and malignant tumor formation. Because of the great clinical heterogeneity, patients may present to different specialists; therefore, the diagnosis may be difficult and delayed. A multidisciplinary specialist care is recommended throughout the lifetime of the patient. The purpose of the article is a review of up-to-date recommendations on NF1 and demonstration of the latest discoveries in this area. In this review, we describe benign and malignant features of NF1, diagnostic strategies, monitoring and treatment of disorders associated with NF1.